Caramel Memories - McClerking, Travis (Cornfield Review, 2020)
A poetry piece meant to create a retrospective snapshot of the wonders of childhood. It aims to emphasize the prevelance of Black family life and its potential to be the cannon portrayal of American suburbia. In a few lines it attempts to explain the joy of a single moment etched into the rings of a growing boy.